A decoupled approach for non-probabilistic reliability-based design optimization. (15th October 2016) - Meng, Zeng; Zhou, Huanlin; Li, Gang; Yang, Dixiong
Highlights: The feasibility of the decoupled approach for NRBDO is proved. A new sequential optimization approach (SOA) is proposed based on CPA. A feasibility-checking criterion for identifying the active or inactive constraints. A mathematical definition is given to distinguish the types of convex models for practical application conveniently. Abstract: Non-probabilistic reliability-based design optimization (NRBDO) offers a powerful tool for structural design when uncertain-but-bounded parameters are considered. Like the reliability-based design optimization (RBDO), the NRBDO application for practical engineering structure is hindered by the huge computational effort involved in the repeated evaluation of non-probabilistic constraints. The decoupled strategy is one of the most efficient RBDO strategies. However, whether it is widely applicable for NRBDO problem remains unknown. In this paper, we make attempts to develop a decoupled strategy for NRBDO convex models based on the concerned performance approach, and propose a sequential optimization approach to handle the deterministic optimization and non-probabilistic reliability analysis sequentially. A new feasibility-checking criterion is further proposed, and the non-probabilistic constraints are divided into active, inactive and violated categories. Since only concerned points of active and violated constraints are calculated accurately, the computational cost associated with non-probabilistic constraint is decreased significantly. Four examples are tested to envelop representative NRBDO problems based on interval set, single-ellipse or multi-ellipse convex model. This way, we show that the decoupled strategies could be promising for a large variety of engineering NRBDO problems.